Effects of oxidation degree and antioxidant addition on the carbon deposition tendency of jatropha biodiesel. Issue 2 (1st June 2023) - Dong, Zhenyu; Li, Fashe; Zhang, Huicong; Duan, Yaozong; Zhao, Zhongjin; Zheng, Yuzeng; Wang, Wenchao
ABSTRACT: The residual carbon value and existent gum content were used to evaluate the carbon deposition tendency of the jatropha biodiesel with different oxidation degrees. The chemical components of residual carbon and existent gum of the jatropha biodiesel were analyzed before and after oxidation by Gas chromatography-mass spectrometry (GC-MS) and infrared spectrometer. The results showed that in the short-term oxidation process, both the residual carbon and existent gum content decreased first, and then increased with oxidation time. In the long-term oxidation process, these two indicators monotonically increased with oxidation time. The residual carbon and existent gum content increased from 1140 mg/100 mL to 11, 300 mg/100 mL and from 0.0272% to 0.277%, respectively. After oxidation, the aromatic compounds in the residual carbon as well as the content in the existent gum such as cyclic ether, carboxylic acid, ketone carbonyl and some fat-soluble impurities significantly increased. The addition of antioxidants showed inhibitive effect on the formation of carbon residue and existent gum. Butylated hydroxytoluene reduced the gum content by 58.3%, and methyl gallate reduced the residual carbon value by 21.1%. These findings prove that the antioxidants can effectively inhibit the auto-oxidation of biodiesel, and thus, reduce the carbon deposition tendency of biodiesel.